Thermogravimetric and kinetic study of thermal degradation of various types of municipal solid waste (MSW) under N2, CO2 and oxy-fuel conditions. (1st June 2022) - Wienchol, Paulina; Korus, Agnieszka; Szlęk, Andrzej; Ditaranto, Mario
Abstract: Oxy-fuel combustion is one carbon capture and sequestration (CCS) technique that uses both O2 and recirculated flue gas as an oxidiser. As a result, the produced gas is composed mainly of CO2 and H2 O, which makes its sequestration more cost-effective. Changing the atmosphere from N2 to CO2 affects combustion behaviour. To study the impact of the atmosphere on the combustion process, the thermal degradation of representative types of municipal solid waste (MSW) under N2, CO2, and O2 /CO2 atmospheres was analysed using a thermogravimetric (TG) instrument. Nonisothermal degradation experiments were conducted, and three heating rates were examined. Isoconversional methods were employed to determine kinetic data. Comparing N2 and CO2 atmospheres, it was found that below 600 °C, the shape of TG curves was not affected significantly. However, above 600 °C under CO2 atmosphere, a second peak appeared, which indicated gasification reactions of the char with carbon dioxide. In the presence of oxygen, the second peak was shifted to lower temperatures, indicating that thermal decomposition with O2 was more rapid. The reported kinetic parameters provide fundamental information on the conversion of solid waste. Thus, they are essential for designing chambers dedicated to the oxy-combustion of waste. Highlights: TGA analysis is performed of waste materials (textiles, spent coffee grounds, PVC). Kinetics of pyrolysis and char burnout is determined using model-free methods. Degree of difficulty in pyrolysis can be ranked as PVC (Ist) < T < SCG < PVC (IIst). Oxidising atmosphere facilitates the degradation process of samples. The Vyazovkin and Friedman methods are most suitable for waste materials.